Sourcebook of criminal justice statistics (U.S. Dept. of Justice, Bureau of Justice Statistics, 2004)
"The Sourcebook of Criminal Justice Statistics brings together data about all aspects of criminal justice in the United States presented in over 600 tables from more than 100 sources. Although the publication of Sourcebook is an annual event, its compilation is an ongoing process. As such, updates of tables and new data sources continually are received and prepared for presentation in the next edition. The site is updated regularly to reflect these new data ... The objective of Sourcebook is to make these data accessible to a wide audience. This electronic edition enables users to access the myriad of data in Sourcebook using automatic searching capabilities that make information retrieval faster and more complete."